Automovasion Carriage for Delivery of Consignments - Shubham, Abhishek Kumar Singh, Shivangi Kaushal, Juhi Singh, Saurabh Samal , Varun (International Journal of Advanced Science and Technology, 2020)
Integrated circuits are in demand to be invetigated for its economical performance. Therefore, it is vialbe to experiment on ternary based operations[7]. A ternary half adder based on ternary multiplexer and logic primitives is proposed and its performance is analyzed in detail. This proposed ternary half is sensibly designed with the simplified expressions using the ternary k-map. The combinational logic blocks for the SUM and CARRY are designed, verified, constructed and simulated with Tanner EDA (130nm) at 1.2 V Automovasion Carriage for Delivery of Consignments is an autonomous vehicle delivery system which uses management chip named Raspberry Pi for its consignments to be delivered automatically. The vehicle can reach the appropriate destination safely and deliver products to the patron without any human intervention. An android app is the controller and tracker of this automated carrier which contains the detailed product information, patron information and location of the respective patron where the product should be delivered. This detailed information is stored in Firebase which is a cloud service and suitable for real time applications. In this paper, an Ultrasonic Sensor in the form of camera is used which can sense all its surrounding objects and a GPS module is also used to navigate the locations and time information anywhere. The purpose of this paper is to simulate and construct the android application and development of the automated product carrier for delivery of goods.